2017
DOI: 10.1016/j.echo.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Maturational Patterns of Systolic Ventricular Deformation Mechanics by Two-Dimensional Speckle-Tracking Echocardiography in Preterm Infants over the First Year of Age

Abstract: Background We aimed to determine the maturational changes in systolic ventricular strain mechanics by two-dimensional speckle tracking echocardiography in extreme preterm neonates from birth to one year of age, and discern the impact of common cardiopulmonary abnormalities on the deformation measures. Methods In a prospective multi-center study of 239 extreme preterm infants (< 29 weeks gestation at birth), left ventricle (LV) global longitudinal strain and systolic strain rate (GLS, GLSRs), interventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
145
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(161 citation statements)
references
References 50 publications
11
145
2
3
Order By: Relevance
“…Our finding is slightly different from those published by other groups where LV strain had remained stable from birth through to 28 days and 36 weeks post‐menstrual age . Levy et al used 2D speckle tracking method to assess LV global strain and reported an initial increase in LV strain in the first 7 days of life but thereafter the LV strain value stabilized until 1 year corrected age. One possible reason for this discrepancy between our finding and other published data could be to the timing of the assessments.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding is slightly different from those published by other groups where LV strain had remained stable from birth through to 28 days and 36 weeks post‐menstrual age . Levy et al used 2D speckle tracking method to assess LV global strain and reported an initial increase in LV strain in the first 7 days of life but thereafter the LV strain value stabilized until 1 year corrected age. One possible reason for this discrepancy between our finding and other published data could be to the timing of the assessments.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with reports assessing LV circumferential and radial strain at the level of the papillary muscle between day 1 and 2 months of age in a healthy term cohort, demonstrating no difference in these parameters during that time period . Interestingly, the persevered measures during the transitional phase are also consistent with the observed patterns of LV longitudinal strain patterns during the transitional period, early neonatal period, and through 1 year of age in premature infants …”
Section: Discussionsupporting
confidence: 92%
“…Longitudinal deformation parameters (strain, SRs, SRe, and SRa) were also obtained from the apical 4‐chamber view for reproducibility analysis to serve as a reference for comparison. Our group has previously published reference values and demonstrated excellent reproducibility for longitudinal deformation measurements in this population …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal strain (S L ) is the most common deformation parameter used in clinical practice in adults. 2DSTE has also been successfully applied in neonatal research and has significantly increased our knowledge of functional cardiac development in preterm infants . Reliability of longitudinal strain (S L ) is superior compared to currently used conventional parameters, and reference values have been established in the term and preterm population .…”
Section: Introductionmentioning
confidence: 99%